Economic Growth Strategy of the Village from the Penta Helix Perspective in Penatih Dangin Puri Village, East Denpasar District, Denpasar City - I Wayan Sutapa; Gede Wirata; Nyoman Dwika Ayu Amrita (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Village economy refers to economic activities that take place in rural areas, which are often dominated by agriculture, livestock and micro, small and medium enterprises. This includes the production and trade of goods and services that meet the needs of local communities as well as the potential for sustainable economic development in the region. Village economic development from the perspective of Pentahelix refers to involving five main parties or groups in the development process, namely; Government, Academics, Business, Community groups, and media. This approach aims to develop the economy in the village area. Each party has an important role; The government provides supportive policies and budgets, academics provide knowledge and innovation, businesses create jobs and investments, community groups fight for the interests and participation of the community, and the media in disseminating information and building public awareness. Through collaboration between these five parties, it is hoped that inclusive and sustainable village economic growth will be realized in order to create the welfare of the village community